1996
DOI: 10.1177/026988119601000212
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of bromocriptine-induced penile erection by chronic lithium in rats

Abstract: In the present study, the effects of chronic lithium pre-treatment (30 days) on penile erection (PE) induced by bromocriptine were investigated in rats. Intraperitoneal administration of the dopamine receptor agonist, bromocriptine (4-32 mg/kg) induced PE in a biphasic manner. The maximum response was obtained with 8 mg/kg of bromocriptine and the effect was decreased with increasing doses of the drug from 8 to 32 mg/kg. When animals were pre-treated with different doses of the D-1 dopamine receptor antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
3
14
0
Order By: Relevance
“…In addition, lithium can inhibit the effects of a number of adenylyl cyclase-linked receptors such as dopamine receptors (Kebabian & Calne 1979;Ebstein et al 1980;Braun & Chase 1986). Therefore the inhibitory effects of lithium may be due to post-receptor mechanism interactions, which was also reported in our previous works (Sharifzadeh et al 1996(Sharifzadeh et al , 1997(Sharifzadeh et al & 1998. The maximum inhibitory effect of lithium was observed after 14 days.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, lithium can inhibit the effects of a number of adenylyl cyclase-linked receptors such as dopamine receptors (Kebabian & Calne 1979;Ebstein et al 1980;Braun & Chase 1986). Therefore the inhibitory effects of lithium may be due to post-receptor mechanism interactions, which was also reported in our previous works (Sharifzadeh et al 1996(Sharifzadeh et al , 1997(Sharifzadeh et al & 1998. The maximum inhibitory effect of lithium was observed after 14 days.…”
Section: Discussionsupporting
confidence: 81%
“…One of the major findings of the present study is that the yawning response induced by apomorphine was decreased in animals pretreated with lithium for 7, 14 and 21 days. Our previous investigations have also shown that lithium can decrease penile erection induced by activation of the dopaminergic system (Dehpour et al 1995;Sharifzadeh et al 1996) and yawning response induced by cholonergic activation (Sharifzadeh et al 1997). It has been reported that lithium causes depletion of cytoplasmic inositol and phosphoinositide turnover (Hallcher & Sherman 1980;Del-Rio et al 1998), which could interfere with the re-synthesis of phosphatidyl inositol bisphosphate, thus influencing the signaling mechanisms operating through the phosphoinositide system.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The major finding of the present study is the yawning response induced by physostigmine was decreased in animals pretreated with chronic lithium. Our previous investigations have also shown that chronic lithium can decrease penile erection induced by activation of dopaminergic system (Dehpour et al 1995 ;Sharifzadeh et al 1996).…”
Section: Discussionmentioning
confidence: 85%
“…Our previous works have shown that chronic lithium can alter responses that are mediated by phosphoinositides pathway (Dehpour et a/. 1995;Sharifzadeh et a/. 1996Sharifzadeh et a/.…”
mentioning
confidence: 99%